Key elements of interventions for heart failure patients with mild cognitive impairment or dementia: A systematic review. (1st January 2020) - Hickman, Louise; Ferguson, Caleb; Davidson, Patricia M; Allida, Sabine; Inglis, Sally; Parker, Deborah; Agar, Meera
Abstract: Background: The purpose of this systematic review was to (a) examine the effects of interventions delivered by a heart failure professional for mild cognitive impairment and dementia on cognitive function, memory, working memory, instrumental activities of daily living, heart failure knowledge, self-care, quality of life and depression; and (b) identify the successful elements of these strategies for heart failure patients with mild cognitive impairment or dementia. Methods and results: During March 2018, an electronic search of databases including CINAHL, MEDLINE, EMBASE and PsycINFO was conducted. All randomised controlled trials, which examined an intervention strategy to help heart failure patients with mild cognitive impairment or dementia cope with self-care, were included. An initial search yielded 1622 citations, six studies were included ( N = 595 participants, mean age 68 years). There were no significant improvements in cognitive function and depression. However, significant improvements were seen in memory ( p =0.015), working memory ( p =0.029) and instrumental activities of daily living ( p =0.006). Nurse led interventions improved the patient's heart failure knowledge ( p =0.001), self-care ( p <0.05) and quality of life ( p =0.029). Key elements of these interventions include brain exercises, for example, syllable stacks, individualised assessment and customised education, personalised self-care schedule development, interactive problem-solving training on scenarios and association techniques to prompt self-care activities. Conclusions: Modest evidence for nurse led interventions among heart failure patients with mild cognitive impairment or dementia was identified. These results must be interpreted with caution in light of the limited number of available included studies.